2018
DOI: 10.1002/ijgo.12457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dual trigger with combination GnRH agonist and hCG versus hCG alone trigger of oocyte maturation for normal ovarian responders

Abstract: Dual trigger of oocyte maturation was not associated with any change in the live delivery rate but was associated with improvements in the quantity and quality of embryos; it could optimize pregnancy outcomes for normal ovarian responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 22 publications
6
32
1
Order By: Relevance
“…In addition, a GnRHa trigger can also activate the GnRH receptors on granulosa cells, which may regulate ovulation 16 . Our results are consistent with many studies of the use of dual trigger for oocyte maturation in normal responders 1,11,12,17 . Though several studies showed that there was no signi cant difference in the number of MII oocytes and the number of 2PN oocytes with the use of dual trigger in comparison to hCG alone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, a GnRHa trigger can also activate the GnRH receptors on granulosa cells, which may regulate ovulation 16 . Our results are consistent with many studies of the use of dual trigger for oocyte maturation in normal responders 1,11,12,17 . Though several studies showed that there was no signi cant difference in the number of MII oocytes and the number of 2PN oocytes with the use of dual trigger in comparison to hCG alone.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, much higher abortion rate was demonstrated in the dual trigger group (17.95% vs. 10.34%), although this difference was not statistically signi cant. Our results agreed with Zhou who reported no difference between the two study groups regarding the implantation rate, clinical pregnancy rate and live birth rate in a retrospective cohort study including a big sample size (220 patients in dual trigger group and 110 control patients) 12 . In addition, two randomized controlled trial (RCT) studies by Shymaa and Alleyassin explored the effect of dual trigger for oocyte maturation on the pregnant outcome in fresh embryo transfer cycles in normal responders 17,20 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Some studies reported a significantly improved ongoing pregnancy rate and live-birth rate in fresh-embryo transfer (FET) cycles for a dual-trigger group compared with the hCG-trigger group in normal responders (1,11). By contrast, several studies have demonstrated that dual trigger of oocyte maturation was not associated with a change in the live-birth rate in FET cycles for normal ovarian responders (12,13). However, those studies did not focus on the cumulative live-birth rate, which provides an all-inclusive success rate for assisted reproductive technology (ART).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effectiveness of dual trigger on uterine receptivity is still controversial as most recent study by Zhou et al . demonstrated that there are no differences in pregnancy outcomes between the dual and hCG only triggers 68 . Our results demonstrated that the dual trigger with low dose of buserelin and hCG tended to improve blastocyst implantation and endometrial steroid signalling (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 93%